2003
DOI: 10.1029/2002rg000114
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐aerosol‐cloud processes in the lower atmosphere

Abstract: [1] Natural terrestrial radioactivity and cosmic ray ionization lead to the formation of air ions and charged aerosol particles even away from regions of active charge separation, such as in thunderstorms. The natural electrified state of the atmosphere has been studied for over a century; however, the effect of ionization on the physical properties of aerosols and clouds has rarely been studied in its own right except in thunderstorms. Here we review the status of our understanding of atmospheric charged part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
338
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(352 citation statements)
references
References 155 publications
(208 reference statements)
8
338
0
6
Order By: Relevance
“…The possible effect of image charges can be important as well but it is not included in this model. The presence of ions at SMEAR II (Laakso et al, 2004), and work by Tinsley et al (2000), Tripathi and Harrison (2001), Harrison and Carslaw (2003) indicate that electrostatic charge image interaction is possible between AP and raindrops. There is not yet a direct experimental account of the role of electric charge in UFP scavenging, and in the rest of the paper we will show results only for neutral particles.…”
Section: Effective Scavenging Coefficientmentioning
confidence: 99%
“…The possible effect of image charges can be important as well but it is not included in this model. The presence of ions at SMEAR II (Laakso et al, 2004), and work by Tinsley et al (2000), Tripathi and Harrison (2001), Harrison and Carslaw (2003) indicate that electrostatic charge image interaction is possible between AP and raindrops. There is not yet a direct experimental account of the role of electric charge in UFP scavenging, and in the rest of the paper we will show results only for neutral particles.…”
Section: Effective Scavenging Coefficientmentioning
confidence: 99%
“…The attractive potential between ions and ions and between ions and the dipole moment (induced or not) of the condensable vapor reduces the thermodynamic barrier for nucleation and hence, enhances the condensational growth (Lovejoy et al, 2004;Nadykto and Yu, 2004). Conflicting views about the relative importance of IMN subsist between modelling studies (see for example Laakso et al, 2002;Harrisson and Carslaw, 2003;Yu et al, 2008) which assess that IMN should be an important source of atmospheric particles and field measurements (see for example Eisele et al, 2006;Manninen et al, 2009) who show that the contribution of IMN to new particle formation in planetary boundary layer (PBL) is less than 10% in average. In any case, the charged fraction of clusters and particles is a good indicator of the presence of neutral clusters and particles.…”
mentioning
confidence: 99%
“…Ion-induced nucleation was invoked to explain the correlation between the global cloudiness and the cosmic rays intensity (Carslaw et al, 2002;Harrison and Carslaw, 2003). The temperature-dependent aerosol chamber measurements on the binary H 2 SO 4 -H 2 O nucleation showed that the neutral particle formation is preferred at low temperatures, while ion-induced particle formation dominates at higher temperatures (Duplissy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%